Vaccination With a Gamma Irradiation-Inactivated African Swine Fever Virus Is Safe But Does Not Protect Against a Challenge - Pikalo, Jutta; Porfiri, Luca; Akimkin, Valerij; Roszyk, Hanna; Pannhorst, Katrin; Kangethe, Richard Thiga; Wijewardana, Viskam; Sehl-Ewert, Julia; Beer, Martin; Cattoli, Giovanni; Blome, Sandra (Frontiers in Immunology, 2022)
African swine fever (ASF) is among the most devastating viral diseases of pigs and wild boar worldwide. In recent years, the disease has spread alarmingly. Despite intensive research activities, a commercialized vaccine is still not available, and efficacious live attenuated vaccine candidates raise safety concerns. From a safety perspective, inactivated preparations would be most favourable. However, both historical and more recent trials with chemical inactivation did not show an appreciable protective effect. Under the assumption that the integrity of viral particles could enhance presentation of antigens, we used gamma irradiation for inactivation. To this means, gamma irradiated ASFV “Estonia 2014” was adjuvanted with either Polygen™ or Montanide™ ISA 201 VG, respectively. Subsequently, five weaner pigs per preparation were immunized twice with a three-week interval. Six weeks after the first immunization, all animals were challenged with the highly virulent ASFV strain “Armenia 2008”. Although ASFV p72-specific IgG antibodies were detectable in all vaccinated animals prior challenge, no protection could be observed. All animals developed an acute lethal course of ASF and had to be euthanized at a moderate humane endpoint within six days. Indeed, the vaccinated pigs showed even higher clinical scores and a higher inner body temperature than the control group. However, significantly lower viral loads were detectable in spleen and liver of immunized animals at the time point of euthanasia. This phenomenon suggests an immune mediated disease enhancement that needs further investigation.